Pengaruh Penambahan Konsentrat Pada Induk Kambing Boerawa Terhadap Litter Size, Bobot Lahir, dan Bobot Sapih Anak Kambing yang Dipelihara Petani Secara Intensif - Adhianto, K (2013)
The goal of this study was to determine the effect of concentrate addition on doe boerawa goat against litter size, birth weight, and weaning weight kid goat keep by farmer in intensive. In this study the animals used are as many as 16 does Boerawa, about 8 months old with an average initial weight of 24 kg. The research is divided into 4 treatment groups with 1 control. Addition of concentrate given since the beginning of the study, pregnant period until weaning kid. The results showed that the addition of different concentrations are not significantly affected litter size (R0; 1,75 +0,96, R1; 1,25+0,50, R2; 1,5+0,58, dan R3; 1,5+0,58), birth weight (R0; 3,40+0,35, R1; 3,37+0,15, R2; 3,39+0,15, dan R3; 3,42+0,18 kg), and weaning weight (R0; 18,81+2,31, R1; 19,20+1,19, R2; 19,20+1,23, dan R3; 19,16+1,23 kg) Boerawa kid goat. Keywords: boerawea goat, birth weight, litter size, weaning weight